Sodium ion positive electrode material precursor, preparation method and application thereof
Through the combination of high-speed stirring and spraying technology, the uniformity and electrochemical performance of the cathode material of sodium ion battery are solved, and the efficient and low-energy-consuming preparation process is achieved, and the performance and production efficiency of the material are improved.
Patent Information
- Application Number
- CN202211249388.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The uniformity and electrochemical properties of the existing sodium ion battery cathode materials are subject to the problems of raw material reaction uniformity, process complexity, and high energy consumption, especially in industrial production, which is difficult to achieve efficient preparation.
Using a combination of high-speed stirring and spraying technology, mix raw materials by stirring once, spraying solvents into pre-granulation during high-speed stirring, stop spraying solvents and lowering the rotation speed to granulate, forming uniform mixed particles, reducing solvent usage and high-temperature drying , reduce energy consumption.
It improves the uniformity and electrochemical performance of sodium ion cathode materials, reduces energy consumption and production costs, avoids waste liquid treatment problems, and improves the processing performance and cycle life of the materials.
Smart Images

Figure CN115893514B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion positive electrode material precursor, a preparation method and an application thereof. Background Art
[0002] In daily life, as an energy-providing product, lithium-ion batteries can be seen everywhere. The current mainstream lithium-ion battery positive electrode materials are lithium cobalt oxide, ternary materials (such as lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide), lithium iron phosphate, and lithium manganese oxide. Among them, lithium cobalt oxide and ternary materials are layered oxides, and the two together account for more than 50% of lithium-ion batteries. As a supplement to lithium-ion batteries, sodium-ion batteries can replace some low-energy density application scenarios to alleviate dependence on lithium resources. An important technical route in the positive electrode materials of sodium-ion batteries is also the layered oxide series, which has a similar process preparation technology to lithium-ion layered oxides, that is, the solid-phase sintering method is used. The preparation process is simple, and this series of materials has better electrochemical properties. Therefore, sodium-ion layered oxide materials have inherent advantages in commercialization and large-scale production.
[0003] Sodium ion layered oxide, namely Na x MO2 (where M is a transition metal such as Ni, Fe, Mn, Co, Cu, Cr, etc.) is usually composed of 3 to 4 transition metals. Sodium ion layered oxides can also be element-doped materials. The more typical materials are NaNi 1-x-y-z Fe y Mn z Me x O2 (where Me represents metal elements such as Al, Mg, Ti, Cu, Cr, and Zr). This material is composed of three or more multi-metal elements, and each element plays a different role in it, so a series of materials with different proportions are derived. Regardless of the proportion between the metal elements, we hope to prepare materials with high uniformity to ensure that the performance of the material is perfectly exerted. Uniformity not only refers to the uniform distribution of each element, but also includes that the material particles have a narrow particle size distribution, that is, the particle size is uniform.
[0004] The simplest preparation method for industrial production of sodium ion layered oxides is solid phase sintering. Common raw materials are oxides of corresponding transition metals, such as NiO, Mn2O3, Fe2O3, CuO, etc. Due to the large variety of raw materials and inconsistent raw material specifications, the reaction uniformity of the material is poor during the solid phase reaction, and the final material particle size distribution is wide and the particle consistency is poor, which seriously affects the processing performance and electrochemical performance of the material.
[0005] In order to solve the problem of material uniformity, the commonly used preparation methods in the industry are co-precipitation precursor method and spray granulation method. The co-precipitation precursor method refers to dripping a multi-metal salt solution such as NiSO4, MnSO4, FeSO4 solution into an alkaline base liquid at a certain speed to perform a co-precipitation reaction to prepare Ni x Fe y Mn z (OH)2 precursor, and then the precursor and the sodium source are evenly mixed to prepare the final positive electrode material through solid phase reaction. In this method, since the precursor is prepared in liquid phase, the particle size distribution of the precursor particles is narrow and the particle size uniformity is high. However, in this method, due to the different solubility products of different metal elements, some of which are even orders of magnitude, it is difficult to prepare precursor particles with uniform element distribution, and the process is complicated. At the same time, due to the liquid phase preparation, a large amount of waste liquid treatment is involved, which has a great impact on the environment. Another spray granulation method is to use various metal oxide raw materials, such as NiO, Fe2O3, Mn2O3, mixed with a sodium source, added to deionized water or ethanol solvent for liquid phase mixing and dispersion, and then the dispersed solution is transferred to a spray drying equipment for spray drying. Due to the atomization effect, the dried slurry will form uniform powder particles, and then the dried particles are solid-phase sintered. This method can also solve the problem of material uniformity. However, since this method requires atomizing the solution in which the raw materials are dispersed, the solid content of the solution cannot be too high, usually only about 20% to 30%. At the same time, the spray drying temperature is as high as 200°C, which will cause high energy consumption and high processing costs. Therefore, it has not been widely used in the industry. Summary of the invention
[0006] In view of the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a sodium ion battery positive electrode material precursor, a preparation method and application thereof, and specifically relates to a sodium ion positive electrode material precursor, a preparation method of a sodium ion positive electrode material precursor, a sodium ion positive electrode material, a preparation method of a sodium ion positive electrode material and a sodium ion battery.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a sodium ion positive electrode material precursor, the method comprising the following steps:
[0009] (1) Mixing:
[0010] The raw materials of the sodium ion positive electrode material are stirred once;
[0011] (2) Pre-granulation:
[0012] The materials after the mixing are stirred once and stirred at a high speed, wherein the rotation speed of the high-speed stirring is greater than or equal to 400 rad / min, and the solvent is sprayed in the form of a spray during the high-speed stirring;
[0013] (3) Granulation:
[0014] Stop spraying the solvent, and perform secondary stirring, wherein the rotation speed of the secondary stirring is less than 400 rad / min, to obtain a sodium ion positive electrode material precursor.
[0015] In the method of the present invention, the rotation speed of high-speed stirring is greater than or equal to 400 rad / min, for example, it can be 400 rad / min, 420 rad / min, 440 rad / min, 460 rad / min, 480 rad / min, 500 rad / min, 525 rad / min, 550 rad / min, 570 rad / min, 600 rad / min, 630 rad / min, 660 rad / min, 700 rad / min, 750 rad / min or 800 rad / min, etc.
[0016] In the method of the present invention, the rotation speed of the secondary stirring is less than 400 rad / min, for example, 350 rad / min, 330 rad / min, 300 rad / min, 275 rad / min, 240 rad / min, 200 rad / min, 180 rad / min, 160 rad / min, 150 rad / min, 125 rad / min, 100 rad / min, 90 rad / min, 80 rad / min or 700 rad / min, etc.
[0017] The present invention provides a method for preparing a sodium ion positive electrode material precursor, wherein the raw materials of the sodium ion positive electrode material are stirred once to obtain a uniformly mixed raw material, and in step (2), the raw materials are stirred at high speed and a solvent is sprayed in the form of a spray during the process, and the solvent is sprayed to wrap and disperse the high-speed stirred powder by using the intermolecular forces, hydrogen bonds and other chemical bonds of the solvent, thereby achieving the effect of pre-granulation, and in step (3), the solvent is stopped from being sprayed and the stirring speed is reduced. In this step, similar powder particles will agglomerate into granules, and at the same time, due to the presence of intermolecular forces, hydrogen bonds and other chemical bonds of the wrapped solvent, repulsive forces will be generated between the particles and dispersed, thereby forming uniform mixed particles, and granulation is completed. The raw materials originally with different morphology specifications are prepared into mixed particles with uniform element distribution and uniform particle size.
[0018] The present invention directly mixes the raw materials of the sodium ion positive electrode material. Generally, there are many types of raw materials, and the specific gravity of different raw materials is different. Especially when the raw material is an ultrafine powder with a particle size of less than 10um, it is more difficult to disperse. The present invention stirs the raw materials once, and then stirs them under the condition of a rotation speed greater than or equal to 400rad / min. When the stirring speed reaches a certain speed, the raw materials have a throwing effect, and the raw materials with different specific gravity can fully contact and rub in the stirring cavity to achieve an ideal dispersion and mixing effect. If the stirring speed is low, the force on the material is small, the cavity cannot be filled with the material, and the ideal dispersion and mixing effect cannot be achieved.
[0019] The method of the present invention can improve the particle distribution of the sodium ion positive electrode material precursor and improve the uniformity of the positive electrode material. The sodium ion positive electrode material precursor is used to synthesize the sodium ion positive electrode material through solid phase reaction, which can improve the processing performance and electrochemical performance of the sodium ion positive electrode material, and the electrochemical performance includes discharge capacity and cycle life.
[0020] Compared with spray drying granulation, the method of the present invention requires a greatly reduced amount of solvent, does not require additional high-temperature drying, greatly reduces preparation energy consumption, and does not have the problem of waste liquid disposal.
[0021] In the method of the present invention, the mixing step of step (1) is necessary. If this step is skipped and the pre-granulation of step (2) is directly carried out, spraying and high-speed stirring are performed during the pre-granulation process. Since the spraying amount of the present invention is relatively low and insufficient to form a dispersing solvent, it will cause serious agglomeration of the same raw materials, and ultimately cause serious segregation of the components of the material and poor consistency.
[0022] The method of the present invention can control the final granulation specifications of the mixed powder by adjusting the rotation speed and the spray amount. In one embodiment, the particle size D50 of the sodium ion positive electrode material precursor is ≤10um, and D50 is, for example, 10um, 9um, 8um, 7um, 6um, 5um, 4um or 3um.
[0023] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0024] Preferably, the raw materials of the sodium ion positive electrode material in step (1) include metal oxide and sodium source.
[0025] Preferably, the metal oxide includes at least one of nickel oxide, manganese oxide, iron oxide and copper oxide.
[0026] Preferably, the metal oxide further includes at least one of aluminum oxide, magnesium oxide, titanium oxide, chromium oxide and zirconium oxide.
[0027] Preferably, the powder particle size D50 of the metal oxide is ≤2um, for example, 2um, 1.8um, 1.6um, 1.5um, 1.4um, 1.2um, 1.0um, 0.8um, 0.5um or 0.3um, etc.
[0028] Preferably, the sodium source in step (1) is Na2CO3.
[0029] Preferably, the powder particle size D50 of the sodium source in step (1) is ≤5um, such as 5um, 4.7um, 4.5um, 4.3um, 4.0um, 3.8um, 3.5um, 3.0um, 2.5um, 2um, 1.8um, 1.6um, 1.5um, 1.4um, 1.2um, 1.0um, 0.8um, 0.5um or 0.3um, etc. By limiting the powder particle size of the above-mentioned metal oxide and the powder particle size of the sodium source, the specific surface area of the raw material can be increased and the reaction activity can be increased.
[0030] Preferably, the powder particle sizes D50 and D90 of the raw materials of the sodium ion positive electrode material in step (1) satisfy: D90≤2.5×D50, thereby ensuring that the uniformity of the raw materials is not too poor and avoiding the final positive electrode material particle size being too large, resulting in a reduction in material capacity.
[0031] As a preferred technical solution of the method of the present invention, the one stirring in step (1) includes: after premixing at a speed of 100rad / min to 150rad / min (for example, 100rad / min, 120rad / min, 125rad / min, 135rad / min or 150rad / min, etc.), increasing the speed to 400rad / min to 450rad / min (for example, 400rad / min, 410rad / min, 420rad / min, 430rad / min, 440rad / min or 450rad / min, etc.) and continuing stirring.
[0032] Preferably, the premixing time is 5 min to 15 min, for example, 5 min, 6 min, 8 min, 10 min, 11 min, 12 min, 13 min or 15 min.
[0033] Preferably, the continued stirring time is 30 min to 45 min, for example, 30 min, 35 min, 37 min, 40 min, 42 min, 43 min or 45 min.
[0034] The layered structure positive electrode material of sodium ion battery generally requires three or more metal oxide raw materials, and the quasi-nanoscale powder of the metal oxide powder particle size D50≤2um has the characteristics of large specific surface area and easy agglomeration. Through the above-mentioned step-by-step mixing method, a variety of raw material components (such as a variety of oxide raw materials and sodium source) can be mixed evenly, which is conducive to the uniform distribution of each element, thereby preparing high-performance sodium ion positive electrode materials.
[0035] As another preferred technical solution of the method of the present invention, the rotation speed of the high-speed stirring in step (2) is 425rad / min~100rad / min, for example, 425rad / min, 450rad / min, 470rad / min, 500rad / min, 525rad / min, 550rad / min, 580rad / min or 600rad / min, etc., preferably 450rad / min~550rad / min.
[0036] Preferably, the high-speed stirring time in step (2) is 10 min to 30 min, such as 10 min, 15 min, 20 min, 25 min or 30 min, etc., preferably 20 min to 30 min.
[0037] Preferably, in step (2), the mass of the solvent sprayed per minute accounts for 0.3% to 0.75% of the material after stirring and mixing once, such as 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65% or 0.7%, etc. If the spraying amount is too small, the solvent is not enough to evenly coat the raw material, resulting in uneven granulation size and wide particle size distribution, which loses the meaning of granulation; if the spraying amount is too large, the raw material will become dry mud, increasing the stirring resistance and causing serious damage to the stirring equipment.
[0038] Preferably, the solvent is water, ethanol or a hydroalcoholic solution.
[0039] In one embodiment, the pre-granulation step described in step (2) is carried out using a high-speed mixer with a spray device, wherein the high-speed mixer with a spray device comprises a mixer body and a spray device, wherein a stirring paddle is arranged inside the mixer body, and the spray device comprises a spray storage device, a ventilation device and a nozzle, wherein the nozzle is located at the edge of the top cover above the wall of the mixer body, and the nozzle is used to spray the solvent into the powder in the mixer body during high-speed mixing.
[0040] Preferably, the rotation speed of the secondary stirring in step (3) is 80rad / min to 100rad / min, for example, 80rad / min, 85rad / min, 88rad / min, 90rad / min, 92rad / min, 94rad / min, 96rad / min or 100rad / min.
[0041] Preferably, the secondary stirring time in step (3) is 30 min to 40 min, for example, 30 min, 33 min, 36 min, 38 min or 40 min.
[0042] Preferably, the granulation step in step (3) further includes the step of reducing the rotation speed and continuing stirring after the secondary stirring.
[0043] Preferably, after the secondary stirring, the rotation speed is reduced to 50rad / min to 80rad / min, for example, 50rad / min, 55rad / min, 60rad / min, 63rad / min, 66rad / min, 70rad / min, 75rad / min or 80rad / min, and stirring is continued for 10min to 20min, for example, 10min, 13min, 15min, 16min, 18min or 20min, etc.
[0044] As a further preferred technical solution of the method of the present invention, the method comprises the following steps:
[0045] S1. Put the metal oxide raw materials NiO, Fe2O3, Mn2O3, CuO powder and Na2CO3 into a high-speed mixer, pre-mix at a speed of 100-150rad / min for 10 minutes, and then mix at a high speed of 400-450rad / min for 30-45 minutes to ensure that the raw material powders are evenly mixed. The particle size D50 of each oxide powder is required to be ≤2um, the particle size D50 of Na2CO3 powder is ≤5um, and the particle size D90 of each raw material is ≤2.5×D50. By controlling the relationship between the self-sufficient D90 and D50 of each raw material, the particle size consistency of the raw materials can be controlled.
[0046] S2. Deionized water or anhydrous ethanol solution is loaded into the spray storage, and the high-speed mixer and spray device are started to pre-granulate at a speed of 450rad / min, and the stirring time is 20min to 30min. Spraying is performed while stirring, and the spraying amount of the atomized liquid is adjusted according to the total amount of the mixed powder, and the amount of the atomized liquid sprayed per minute is 0.3% / min to 0.75% / min of the total amount of the powder.
[0047] S3, close the spray device, reduce the speed of the high-speed stirrer to 80-100 rad / min, carry out stirring and granulation, the stirring time is 30min-40min, continue to reduce the speed of the high-speed stirrer to 50-80 rad / min, the stirring time is 10-20min, complete the granulation, and obtain the sodium ion positive electrode material precursor.
[0048] In this preferred technical solution, after step S1, each raw material is fully mixed, and each element is evenly distributed in the mixed powder. When step S2 is performed for high-speed stirring, the spray device is turned on, and the solvent is sprayed into the high-speed mixer while stirring, so that the mixed powder is wrapped by the solvent and wetted evenly. Then step S3 is performed to reduce the stirring speed. In this step, similar powder particles will agglomerate into granules; at the same time, due to the intermolecular forces between the wrapped solvents, the existence of chemical bonds such as hydrogen bonds, the particles will generate repulsive forces and disperse. After mixing in step S1 and granulation in steps S2 and S3, the raw materials with different morphology and specifications are prepared into mixed particles with uniform element distribution and uniform particle size.
[0049] In a second aspect, the present invention provides a sodium ion positive electrode material precursor prepared by the method described in the first aspect.
[0050] In a third aspect, the present invention provides a sodium ion positive electrode material, wherein the sodium ion positive electrode material is prepared by a solid phase reaction of the sodium ion positive electrode material precursor.
[0051] In a fourth aspect, the present invention provides a method for preparing the sodium ion positive electrode material as described in the third aspect, the method comprising the following steps:
[0052] The sodium ion positive electrode material precursor described in the second aspect is sintered to obtain the sodium ion positive electrode material.
[0053] Preferably, the sintering system includes: keeping at a first temperature for a period of time t1, heating to a second temperature and keeping for a period of time t2, wherein the second temperature is 1000℃~1100℃, for example 1000℃, 1010℃, 1020℃, 1030℃, 1050℃, 1060℃, 1070℃, 1080℃ or 1100℃, etc.
[0054] Preferably, the first temperature is 150°C to 200°C, for example, 150°C, 160°C, 165°C, 170°C, 180°C, 190°C or 200°C.
[0055] Preferably, t1 is 2 h to 3 h, for example, 2 h, 2.1 h, 2.2 h, 2.4 h, 2.5 h, 2.8 h or 3 h.
[0056] Preferably, the temperature is increased from the first temperature to the second temperature in a gradient heating manner, and the gradient heating includes: heating from the first temperature to T1 at a first heating rate, then reducing the heating rate to heat to T2, and then continuing to reduce the heating rate to heat to the second temperature.
[0057] Preferably, the first heating rate is 4°C / min to 5°C / min, for example, 4°C / min, 4.2°C / min, 4.5°C / min or 5°C / min, and T1 is 500°C to 700°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 630°C, 660°C, 680°C or 700°C, etc.
[0058] Preferably, the second heating rate is 2°C / min to 3°C / min, for example, 2°C / min, 2.5°C / min, 2.7°C / min or 3°C / min, and T2 is 800°C to 1000°C, for example, 800°C, 825°C, 850°C, 870°C, 900°C, 925°C, 950°C, 975°C or 1000°C, etc.
[0059] Preferably, during the sintering process, air is continuously introduced, and the ventilation rate is preferably 1L / min to 10L / min, such as 1L / min, 2L / min, 2.5L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min or 10L / min. The sintering reaction requires the participation of oxygen, and the CO2 waste gas needs to be removed. The purpose of introducing air is to supplement the oxygen required for the reaction and to form a positive pressure in the furnace body to remove waste gas. Depending on the proportion of raw materials, the amount of oxygen required for the reaction is different; and the exhaust volume is different for different sintering processes. Therefore, it is necessary to dynamically adjust the ventilation volume according to the actual situation.
[0060] In one embodiment, the method for preparing the sodium ion positive electrode material comprises the following steps:
[0061] The sodium ion cathode material precursor is loaded into a sagger and placed in an atmosphere furnace for solid phase reaction. The sintering system of the solid phase reaction is: first, the temperature is raised to 150℃~200℃ at a heating rate of 1℃ / min~5℃ / min, and kept at this temperature for 2h~3h, then the temperature is raised to 500℃~700℃ at a heating rate of 4℃ / min~5℃ / min, and then the temperature is raised to 800℃~1000℃ at a heating rate of 2℃ / min~3℃ / min, and the temperature is further reduced to 1℃ / min~1.5℃ / min to 1000℃~1100℃ and kept for 5h~15h, and then cooled with the furnace. During the entire reaction process, air needs to be continuously introduced at a ventilation rate of 1L / min~10L / min.
[0062] The cooled material is taken out, and after coarse crushing, fine grinding and screening, a sodium ion layered structure positive electrode material is obtained.
[0063] In a fifth aspect, the present invention provides a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the sodium ion positive electrode material described in the third aspect.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention provides a method for preparing a sodium ion positive electrode material precursor, wherein the raw materials of the sodium ion positive electrode material are stirred once to obtain a uniformly mixed raw material, a solvent is sprayed in the form of a spray while stirring at a high speed to achieve a pre-granulation effect, and the solvent is stopped from being sprayed and the stirring speed is reduced to complete the granulation. The raw materials originally having different morphologies and specifications are prepared into mixed particles with uniform element distribution and uniform particle size.
[0066] (2) High-speed mixing and spraying technology are combined to perform high-speed mixing granulation, thereby reducing energy consumption and improving production efficiency while ensuring granulation uniformity. Finally, a sodium ion layered structure positive electrode material with good uniformity is prepared, and the electrochemical properties of the material are improved, including discharge capacity and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is the particle size distribution of the sodium ion layered structure positive electrode material of Example 1.
[0068] Figure 2 This is the particle size distribution of the sodium ion layered structure positive electrode material of Comparative Example 1. DETAILED DESCRIPTION
[0069] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0070] In one embodiment, a high-speed mixer with a spray device is used to carry out the pre-granulation step of step (2) and the granulation step of step (3). The high-speed mixer with a spray device comprises a mixer body and a spray device. A stirring paddle is arranged in the mixer body. The spray device comprises a spray storage, a ventilation device and a nozzle. The nozzle is located at the edge of the top cover above the wall of the mixer body. The nozzle is used to spray the solvent into the powder in the mixer body during high-speed mixing.
[0071] Example 1
[0072] This embodiment provides a sodium ion positive electrode material precursor, and the preparation method includes the following steps:
[0073] (1) Mixing:
[0074] The required metal oxide NiO (D50 = 1.2um, D90 = 2.7um), Fe2O3 (D50 = 0.9um, D90 = 1.8um), Mn2O3 (D50 = 1.8um, D90 = 4.3um), CuO (D50 = 1.5um, D90 = 3.6um) powders and Na2CO3 (D50 = 4.3um, D90 = 9.8um) are put into a high-speed mixer according to the metal element molar ratio of Na:Ni:Fe:Mn:Cu = 100:20:33:33:14. The total amount of powder input is 30kg. Premix for 10 minutes at a rotation speed of 120rad / min, and then mix at a high speed for 30 minutes at a rotation speed of 450rad / min.
[0075] (2) Pre-granulation:
[0076] Deionized water was placed in the spray storage, and the high-speed mixer and the spray device were started. Pre-granulation was performed at a speed of 450 rad / min, and the stirring time was 20 min. Spraying was performed while stirring, and the spraying amount of the atomized liquid was adjusted to 0.15 kg / min.
[0077] (3) Granulation: Turn off the spray device, reduce the speed of the high-speed stirrer to 80 rad / min, and mix for 30 min to complete granulation to obtain a sodium ion positive electrode material precursor.
[0078] This embodiment also provides a method for preparing a sodium ion layered structure positive electrode material using the above sodium ion positive electrode material precursor, comprising the following steps:
[0079] The granulated powder is placed in a sagger and placed in an atmosphere furnace for solid phase reaction. The sintering system of the solid phase reaction is: first, the temperature is raised to 150°C at a heating rate of 5°C / min, and kept for 2 hours, then the temperature is raised to 650°C at a heating rate of 5°C / min, and then the temperature is raised to 950°C at a heating rate of 2°C / min, and then the heating rate is further reduced to 1°C / min to 1050°C, and the temperature is kept at 1050°C for 10 hours, and then cooled with the furnace. During the entire reaction process, air needs to be continuously introduced at a ventilation rate of 2L / min.
[0080] The cooled material is taken out, and the desired sodium ion layered structure positive electrode material is obtained after coarse crushing, fine grinding and screening.
[0081] Figure 1It is the particle size distribution of the sodium ion layered structure positive electrode material of Example 1. It can be seen from the figure that the sample after granulation and sintering has a narrow particle size distribution, and the peak shape is high and thin. The material particle size distribution is between 1 and 40um. There is no micropowder (powder of less than 1um) and extra-large particle size (powder of more than 50um) material, indicating that the material consistency is good.
[0082] Example 2
[0083] This embodiment provides a sodium ion positive electrode material precursor, and the preparation method includes the following steps:
[0084] (1) Mixing:
[0085] The required metal oxide NiO (D50 = 1.2um, D90 = 2.7um), Fe2O3 (D50 = 0.9um, D90 = 1.8um), Mn2O3 (D50 = 1.8um, D90 = 4.3um), CuO (D50 = 1.5um, D90 = 3.6um) powders and Na2CO3 (D50 = 4.3um, D90 = 9.8um) are put into a high-speed mixer according to the metal element molar ratio of Na:Ni:Fe:Mn:Cu = 100:20:33:33:14. The total amount of powder input is 30kg. Premix for 5 minutes at a rotation speed of 135rad / min, and then mix at a high speed of 45 minutes at a rotation speed of 400rad / min.
[0086] (2) Pre-granulation:
[0087] Deionized water was placed in the spray storage, and the high-speed mixer and the spray device were started. Pre-granulation was performed at a speed of 500 rad / min, and the stirring time was 20 min. Spraying was performed while stirring, and the spraying amount of the atomized liquid was adjusted to 0.1 kg / min.
[0088] (3) Granulation: Turn off the spray device, reduce the speed of the high-speed stirrer to 90 rad / min, mix for 30 min, and continue to reduce the speed of the high-speed stirrer to 50 rad / min, mix for 10 min, complete granulation, and obtain a sodium ion positive electrode material precursor.
[0089] This embodiment also provides a method for preparing a sodium ion layered structure positive electrode material using the above sodium ion positive electrode material precursor, comprising the following steps:
[0090] The granulated powder is placed in a sagger and placed in an atmosphere furnace for solid phase reaction. The sintering system of the solid phase reaction is: first, the temperature is raised to 175°C at a heating rate of 3°C / min, and kept warm for 2.5 hours, then the temperature is raised to 700°C at a heating rate of 4°C / min, and then the temperature is raised to 900°C at a heating rate of 3°C / min, and then the heating rate is further reduced to 1.5°C / min to 1000°C, and the temperature is kept at 1000°C for 15 hours, and then cooled with the furnace. During the entire reaction process, air needs to be continuously introduced at a ventilation rate of 5L / min.
[0091] The cooled material is taken out, and the desired sodium ion layered structure positive electrode material is obtained after coarse crushing, fine grinding and screening.
[0092] Example 3
[0093] This embodiment provides a sodium ion positive electrode material precursor, and the preparation method includes the following steps:
[0094] (1) Mixing:
[0095] The required metal oxide NiO (D50 = 1.2um, D90 = 2.7um), Fe2O3 (D50 = 0.9um, D90 = 1.8um), Mn2O3 (D50 = 1.8um, D90 = 4.3um), CuO (D50 = 1.5um, D90 = 3.6um) powders and Na2CO3 (D50 = 4.3um, D90 = 9.8um) are put into a high-speed mixer according to the metal element molar ratio of Na:Ni:Fe:Mn:Cu = 100:20:33:33:14. The total amount of powder input is 30kg. It is pre-mixed at a rotation speed of 130rad / min for 8min, and then mixed at a high speed at 425rad / min for 40min.
[0096] (2) Pre-granulation:
[0097] Deionized water was placed in the spray storage, and the high-speed mixer and the spray device were started. Pre-granulation was performed at a speed of 550 rad / min, and the stirring time was 20 min. Spraying was performed while stirring, and the spraying amount of the atomized liquid was adjusted to 0.2 kg / min.
[0098] (3) Granulation: Turn off the spray device, reduce the speed of the high-speed stirrer to 85 rad / min, and mix for 35 min to complete granulation to obtain a sodium ion positive electrode material precursor.
[0099] This embodiment also provides a method for preparing a sodium ion layered structure positive electrode material using the above sodium ion positive electrode material precursor, comprising the following steps:
[0100] The granulated powder is placed in a sagger and placed in an atmosphere furnace for solid phase reaction. The sintering system of the solid phase reaction is: first, the temperature is raised to 200°C at a heating rate of 5°C / min, and kept for 2 hours, then the temperature is raised to 680°C at a heating rate of 5°C / min, and then the temperature is raised to 950°C at a heating rate of 2°C / min, and then the heating rate is further reduced to 1°C / min to 1075°C, and the temperature is kept at 1075°C for 8 hours, and then cooled with the furnace. During the entire reaction process, air needs to be continuously introduced at a ventilation rate of 7L / min.
[0101] The cooled material is taken out, and the desired sodium ion layered structure positive electrode material is obtained after coarse crushing, fine grinding and screening.
[0102] Example 4
[0103] The difference from Example 1 is that in the step (2) of pre-granulation, the spraying amount of the atomized liquid is 0.05 kg / min.
[0104] Example 5
[0105] The difference from Example 1 is that in the step (2) of pre-granulation, the spraying amount of the atomized liquid is 0.25 kg / min.
[0106] Example 6
[0107] The difference from Example 1 is that the rotation speed of granulation in step (3) is 300 rad / min.
[0108] Example 7
[0109] The difference from Example 1 is that NiO (D50=2.4um, D90=8.3um), Fe2O3 (D50=0.9um, D90=1.8um), Mn2O3 (D50=5.6um, D90=19.2um), CuO (D50=1.5um, D90=6.6um) powders, and Na2CO3 (D50=5.9um, D90=13.5um).
[0110] Example 8
[0111] The difference from Example 1 is that in the method for preparing a sodium ion layered structure positive electrode material using a sodium ion positive electrode material precursor, the sintering system of the solid phase reaction is: first, the temperature is raised to 150°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours, then the temperature is raised to 1050°C at a heating rate of 5°C / min, and the temperature is kept at 1050°C for 10 hours, and then cooled with the furnace. During the entire reaction process, air needs to be continuously introduced at a ventilation rate of 2L / min.
[0112] Comparative Example 1
[0113] The difference from Example 1 is that the steps of step (2) pre-granulation and step (3) granulation are not performed.
[0114] Figure 2 This is the particle size distribution of the sodium ion layered structure positive electrode material of Example 1. It can be seen from the figure that the particle size distribution of the material is relatively wide, and there are many micropowders with a particle size of less than 1um. The presence of these micropowders will lead to the intensification of the side reaction between the material and the electrolyte during the operation of the battery cell, resulting in the destruction of the positive electrode material structure and the failure of the battery cell such as bloating. At the same time, there are also many extra-large particles with a particle size of more than 50um in the material. The presence of large particles will greatly affect the performance of the material capacity, resulting in a decrease in the energy density of the battery cell.
[0115] Comparative Example 2
[0116] The difference from Example 1 is that in the step (2) of pre-granulation, the rotation speed is 350 rad / min.
[0117] Comparative Example 3
[0118] The difference from Example 1 is that in the granulation step (3), the rotation speed is 450 rad / min.
[0119] Comparative Example 4
[0120] The preparation method of the sodium ion positive electrode material precursor of this comparative example comprises the following steps:
[0121] The raw material of the sodium ion positive electrode material is directly mixed with the solvent. The mixing process is pre-mixing at a rotation speed of 120 rad / min for 10 minutes, and then high-speed mixing at a rotation speed of 450 rad / min for 50 minutes. The mixed solution is sprayed and granulated to obtain a sodium ion positive electrode material precursor.
[0122] Performance Characterization
[0123] Material gram capacity and cycle life test:
[0124] The sodium ion layered structure positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-5 were mixed with SP and PVDF in a mass ratio of 90:5:5, a certain amount of NMP solvent was added and stirred evenly, coated on a 15 um aluminum foil, and dried and cut to obtain a positive electrode sheet.
[0125] The positive electrode sheet, PE separator and negative electrode sheet were assembled into an oral battery and the electrochemical performance was tested.
[0126] Gram capacity test: charge and discharge voltage range is 2.0V~4.0V, charge and discharge current is 0.1C / 0.1C. Cycle 3 times and take the average value.
[0127] Cycle performance test: the charge and discharge voltage range is 2.0V~4.0V, the charge and discharge current is 0.5C / 0.5C, when the discharge capacity is lower than 80% of the initial discharge capacity, the test is terminated and the number of cycles is recorded.
[0128] Table 1 Electrochemical performance
[0129]
[0130] As can be seen from Table 1, after granulation, the particle size distribution consistency of the precursor is good, and the sodium ion positive electrode material after sintering also has good particle consistency. There will be no extra-large particles and micropowders, so it has the advantages of high gram capacity and good cycle performance. However, products that have not been granulated or whose granulation process control is not within the scope of the present invention have a bucket effect due to the large difference in particle size between particles, and cannot take into account both gram capacity and energy density, and even have poor performance in these two performances.
[0131] By comparing Example 1 with Examples 4-5, it can be seen that the spray volume needs to be within an appropriate range. A smaller spray volume cannot fully coat the powder, so that the dry powder is still in a dispersed state, and the prepared precursor particle size is smaller, affecting the cycle performance; a higher spray volume makes the powder more easily agglomerated due to the interaction between solvents, and larger particles are likely to appear, which will ultimately affect the capacity performance and cycle performance of the material.
[0132] By comparing Example 1 with Example 6 and Comparative Examples 2-3, it can be seen that the granulation rotation speed will also significantly affect the material properties. If the rotation speed is too high, the powder will be too scattered and the material circulation performance will be reduced; if the rotation speed is too low, the dispersion effect cannot be achieved, the material particle size is too large, and the gram capacity is reduced.
[0133] By comparing Example 1 with Example 7, it can be seen that the particle size of the raw material has a great influence on the final performance of the material. If the difference in the particle size distribution of the raw material is too large, even after the granulation process, the particle size distribution of the granulated material will be wider, thereby reducing the electrochemical performance of the material.
[0134] By comparing Example 1 with Example 8, it can be seen that during the sintering process, the sintering heating rate is not changed, resulting in uneven heating of the material during the high-temperature grain growth stage, thereby widening the particle size distribution of the finished product and reducing the electrochemical performance of the material.
[0135] By comparing Example 1 with Comparative Example 1, it can be seen that even if the particle size distribution of the raw materials is controlled without going through a granulation process, due to the self-activity of the quasi-nanoscale materials, the materials will agglomerate to form irregularly sized particles, affecting the electrochemical properties of the materials.
[0136] By comparing Example 1 with Comparative Example 4, it can be seen that directly adding a small amount of solvent for mixing without dispersion cannot achieve a good dispersion effect, resulting in obvious deterioration of material properties.
[0137] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a sodium ion positive electrode material precursor, It is characterized in that The method comprises the following steps: (1) Mixing: The raw materials of the sodium ion positive electrode material are stirred once. In step (1), the raw materials of the sodium ion positive electrode material are metal oxides and sodium sources, and the powder particle sizes D50 and D90 of the raw materials of the sodium ion positive electrode material satisfy the following conditions: D90≤2.5×D50; The stirring in step (1) comprises: premixing at a speed of 100 rad / min to 150 rad / min, increasing the speed to 400 rad / min to 450 rad / min and continuing stirring; (2) Pre-granulation: The materials after the first stirring and mixing are subjected to high-speed stirring, wherein the rotation speed of the high-speed stirring is greater than or equal to 400 rad / min, and during the high-speed stirring, a solvent is sprayed in the form of a spray, and the mass of the solvent sprayed per minute accounts for 0.3% to 0.75% of the materials after the first stirring and mixing; (3) Granulation: Stop spraying the solvent, and perform secondary stirring, wherein the rotation speed of the secondary stirring is less than 400 rad / min, to obtain a sodium ion positive electrode material precursor.
2. The method according to claim 1, It is characterized in that The metal oxide includes at least one of nickel oxide, manganese oxide, iron oxide and copper oxide.
3. The method according to claim 1, It is characterized in that The metal oxide further includes at least one of aluminum oxide, magnesium oxide, titanium oxide, chromium oxide and zirconium oxide.
4. The method according to claim 1, It is characterized in that The powder particle size D50 of the metal oxide is ≤2um.
5. The method according to claim 1, It is characterized in that The sodium source in step (1) is Na 2 CO 3 .
6. The method according to claim 1, It is characterized in that The powder particle size D50 of the sodium source in step (1) is ≤5um.
7. The method according to claim 1, It is characterized in that The premixing time is 5 min to 15 min.
8. The method according to claim 1, It is characterized in that The stirring time is 30 to 45 minutes.
9. The method according to claim 1, It is characterized in that The rotation speed of the high-speed stirring in step (2) is 425rad / min to 600rad / min.
10. The method according to claim 9, It is characterized in that The rotation speed of the high-speed stirring in step (2) is 450rad / min to 550rad / min.
11. The method according to claim 1, It is characterized in that The time of the high-speed stirring in step (2) is 10 min to 30 min.
12. The method according to claim 11, It is characterized in that The time of the high-speed stirring in step (2) is 20 min to 30 min.
13. The method according to claim 1, It is characterized in that The solvent is water, ethanol or a hydroalcoholic solution.
14. The method according to claim 1, It is characterized in that The rotation speed of the secondary stirring in step (3) is 80 rad / min to 100 rad / min.
15. The method according to claim 1, It is characterized in that The time of the secondary stirring in step (3) is 30 min to 40 min.
16. The method according to claim 1, It is characterized in that The granulation step of step (3) further includes the step of reducing the rotation speed and continuing stirring after the secondary stirring.
17. The method according to claim 16, It is characterized in that After the secondary stirring, the rotation speed is reduced to 50 rad / min to 80 rad / min, and stirring is continued for 10 min to 20 min.
18. A sodium ion positive electrode material precursor prepared by the method according to any one of claims 1 to 17.
19. A sodium ion positive electrode material, It is characterized in that The sodium ion positive electrode material is prepared by solid phase reaction of the sodium ion positive electrode material precursor according to claim 18.
20. A method for preparing the sodium ion positive electrode material as claimed in claim 19, It is characterized in that The method comprises the following steps: The sodium ion positive electrode material precursor according to claim 18 is sintered to obtain the sodium ion positive electrode material.
21. The method according to claim 20, It is characterized in that The sintering system includes: keeping the temperature at a first temperature for a period of time t 1 , heat to the second temperature and keep warm for a period of time t 2 , wherein the second temperature is 1000°C to 1100°C.
22. The method according to claim 21, It is characterized in that The first temperature is 150°C to 200°C.
23. The method according to claim 21, It is characterized in that t 1 2h to 3h.
24. The method according to claim 21, It is characterized in that The temperature is raised from the first temperature to the second temperature in a gradient heating manner, wherein the gradient heating comprises: raising the temperature from the first temperature to T at a first heating rate 1 Then, the heating rate is reduced to the second heating rate, and the temperature is raised to T 2 , continue to reduce the heating rate and heat to the second temperature.
25. The method according to claim 24, It is characterized in that The first heating rate is 4°C / min to 5°C / min, T 1 It is 500℃~700℃.
26. The method according to claim 24, It is characterized in that The second heating rate is 2°C / min to 3°C / min, T 2 It is 800℃~1000℃.
27. The method according to claim 20, It is characterized in that During the sintering process, air is continuously introduced at a ventilation rate of 1 L / min to 10 L / min.
28. A sodium ion battery, It is characterized in that The positive electrode of the sodium ion battery includes the sodium ion positive electrode material according to claim 19.
